Bureaucratic Reform: The Main Means of Corruption Eradication in Indonesia - Muttaqin, Andhyka (International Journal of Psychosocial Rehabilitation, 2020)
Bureaucratic reform that developed in Indonesia since 1998 is now a major vehicle for government administration including the officials in central and regional governments. In relation to government administration, bureaucracy as the key to implementing public services contains various development programs and government policies. However, in reality, a bureaucracy that carries general tasks and development programs from the government is often articulated differently by the public. They feel that public services in government affairs are a long and convoluted process. As a result, bureaucracy always gets a negative image from the public. This can burden the development of the bureaucracy itself (especially in terms of public services). Indonesia was the first country in Asia to issue a special regulation on eradicating corruption in 1958. To date, the regulations on corruption still exist but the success of its implementation is still very far to be achieved. In essence, bureaucratic reform in Indonesia is the main supporting factor to eradicate corruption.